2015
DOI: 10.1179/2045772315y.0000000051
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of local profound hypothermia and the possible mechanism after experimental spinal cord injury in rats

Abstract: Objective: The primary focus of this study was to investigate the effects of local profound hypothermia and to explore the possible mechanism in adult rats with spinal cord injury. Study Design and Methods: Spinal cord injury models were established by placing aneurysm clips on T10. An epidural perfusion device was applied to maintain a steady temperature (18°C) for 120 min with gradual rewarming to 37°C Total hypothermic duration lasted up to about 170 min. The expression of axon regeneration inhibitors was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Of the 24 preclinical studies ( Table 1 ), most ( n = 21) employed a thoracic spinal cord model [ 5 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Twelve studies employed local cooling, eleven used systemic hypothermia, and one evaluated both application modalities.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 24 preclinical studies ( Table 1 ), most ( n = 21) employed a thoracic spinal cord model [ 5 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Twelve studies employed local cooling, eleven used systemic hypothermia, and one evaluated both application modalities.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, epidural perfusion was used in rats after SCI to induce local hypothermia (18°C) for 170 min with gradual rewarming to 37°C. Several beneficial effects were observed in rats subjected to hypothermia: downregulation of axon regeneration inhibitors (RhoA, ROCK-II, NG2, Neurocan, Brevican, and Nogo-A), decreased demyelination and enhanced axon regeneration, which ultimately resulted in recovery of hindlimb function (Xu et al, 2016). After the observation of promising results in rats, it was necessary to verify the effects of hypothermia in larger animal models (Kwon et al, 2015).…”
Section: Local Hypothermiamentioning
confidence: 99%
“…In general, these studies showed that hypothermia is more effective when initiated early after injury and lasts for a longer time. Shorter duration may require more profound cooling to achieve similar effect ( 35 ). In general, these data suggest that long periods of local hypothermia are tolerated well and may improve long-term tissue sparing and functional outcome ( 14 , 35 , 40 43 , 47 , 57 , 87 ).…”
Section: Effects Of Hypothermia In Experimentsmentioning
confidence: 99%
“…Hypothermia also delays glutathione release, reduces oxidative stress and increases spinal cord tolerance to ischemia ( 23 26 ). There are also numerous articles illustrating the neuroprotective effect of hypothermia on neural stem cell differentiation and survival ( 15 , 27 35 ).…”
Section: Introductionmentioning
confidence: 99%